The audio industry: The state of our science and art - Toole, Floyd E. (Canadian Acoustics, 2002)
A report on the utility of science in the service of art is presented. Electromechanical devices like loudspeaker operate over 10 octaves, with a dynamic range of 105 dB or more, delivering sound to ears through rooms that are completely unpredictable in their size, shape, layout and acoustical characteristics. The existing science can yield more consistently good recordings and it can ensure that the finer qualities of the audio arts can be reliably delivered to our homes.